PELAYANAN RAWAT INAP PUSKESMAS SUNGAI PAKNING KEC.BUKIT BATU KAB. BENGKALIS - Sabela, Robi; Khairani, Tuti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Abstract: Service Take Care Of To Lodge Puskesmas Sungai Pakning Kec. Bukit Batu Kab. Bengkalis. This study aimed to know Take Care To Lodge sevice at Puskesmas Sungai Pakning, and to know factors resistor of execution of service at puskesmas sungai pakning. Indicator used at this research is according to theory concept of Zeithaml saying that service can be measured with indicator as following : Realibility, Responsive, Insurance, Emphaty, Including, indicator to know resistor in execution of service. Research method have the caracter of Qulitative descriptive, data collecting used by observatation method and interview. Of research rusult can know that service Take care of to Lodge at puskesmas Sungai Pakning the incluiding at category”not yet is maximal”, while factors esistor of execution of service take care of to lodge at puskesmas Sungai Pakning is officer attitude, coherence of leader and facilities.Key Word: Public Service, Take Care To Lodge, Puskesmas.